2016
DOI: 10.1016/j.psyneuen.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in corticotropin releasing factor-evoked behavior and activated networks

Abstract: Hypersecretion of corticotropin releasing factor (CRF) is linked to the pathophysiology of major depression and post-traumatic stress disorder, disorders that are more common in women than men. Notably, preclinical studies have identified sex differences in CRF receptors that can increase neuronal sensitivity to CRF in female compared to male rodents. These cellular sex differences suggest that CRF may regulate brain circuits and behavior differently in males and females. To test this idea, we first evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 71 publications
3
53
1
Order By: Relevance
“…Consistent with the current hypotheses that CRF mediates the anxiety response differently in males and females, this study showed that higher doses of CRF resulted in increased anxious behaviors for female rats compared to male rats [29••]. Interestingly, there seems to be an interaction with female gonadal hormones as the female rats in their proestrous phase (higher ovarian hormones) showed even more anxious behaviors than females in the diestrous phase.…”
Section: Sex Differences In the Physiologic Response To Traumasupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with the current hypotheses that CRF mediates the anxiety response differently in males and females, this study showed that higher doses of CRF resulted in increased anxious behaviors for female rats compared to male rats [29••]. Interestingly, there seems to be an interaction with female gonadal hormones as the female rats in their proestrous phase (higher ovarian hormones) showed even more anxious behaviors than females in the diestrous phase.…”
Section: Sex Differences In the Physiologic Response To Traumasupporting
confidence: 85%
“…Recent evidence in clinical and preclinical studies have also pointed to sex differences in hypothalamic pituitary adrenal (HPA) axis and autonomic response to threat, contributing to risk for PTSD and post-traumatic stress symptoms in females compared to males [27•, 28••, 29••, 30]. …”
Section: Sex Differences In the Physiologic Response To Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that ovarian hormones and the effects of CRF interact to impact attention. We performed functional connectivity analyses to assess circuits activated by central administration of CRF (as measured by cFOS) and compared how sex and cycle stage altered these circuits [173,174]. Of relevance for SAT, functional connectivity between the NBM and mPFC in rats treated with CRF is different in proestrous females than in both diestrous females and males.…”
Section: Sex Differences In the Cholinergic-attention Systemmentioning
confidence: 99%
“…Almost all Japanese firefighters are men, 69,70 but previous research has shown that the association between corticotropin-releasing factor level and PTSD symptoms differs by gender. 71,72 It is possible that not including gender as a confounding factor (because of the absence of women in the sample) changed the observed associations with PTSD symptoms. Second, this was a crosssectional study, and negative associations observed for rescue operations do not necessarily indicate an effect on probable PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%